Controlling Long‐Distance Photoactuation with Protein Additives. Issue 18 (19th April 2020) - Zhao, Jian; Li, Qian; Miao, Bianliang; Pi, Hemu; Yang, Peng
Abstract: Long‐distance wireless actuation indicates precise remote control over materials, sensors, and devices that are widely utilized in biomedical, defence, disaster relief, deep ocean, and outer space applications to replace human work. Unlike radio frequency (RF) control, which has low tolerance toward electromagnetic interference (EMI), light control represents a promising method to overcome EMI. Nonetheless, long‐distance light‐controlled wireless actuation able to compete with RF control has not been achieved until now due to the lack of highly light‐sensitive actuator designs. Here, it is demonstrate that amyloid‐like protein aggregates can organize photomodule single‐layer reduced graphene oxide (rGO) into a well‐defined multilayer stack to display long‐distance photoactuation. The amyloid‐like proteinaceous component docks the rGO layers together to form a hybrid film, which can reliably adhere onto various material surfaces with robust interfacial adhesion. The sensitive photothermal effect and a fast bending in 1 s to switch a circuit are achieved after forming the film on a plastic substrate and irradiating the bilayer film with a blue laser from 100 m away. A photoactuation distance of 50 km can be further extrapolated based on a commercial high‐power laser. This study reveals the great potential of amyloid‐like aggregates in remote light control of robots and devices. Abstract : The realization of long‐distance photoactuation (e.g., tens of meters) remains a remarkable challenge. By forming an amyloid‐protein/reduced graphene oxide (rGO) hybrid film on the polyethylene substrate, a laser‐controlled long‐distance bilayer actuator that can trigger sensitive actuation from ≈100 m away is successfully developed. Moreover, a photoactuation distance of 50 km can be further extrapolated based on commercial high‐power laser.